PRELIMINARY RESULTS OF GROUNDWATER RECHARGE EXPERIMENTS IN LARISA PREFECTURE - Soulios, G.; Voudouris, K.; Kalfountzos, D.; Kaklis, T.; Sotiriadis, M.; Alexiou, J.; Kotsopoulos, S. (Bulletin of the Geological Society of Greece, 2007)
Thessaly is the most important agricultural region in Greece and their economic development is influenced by the availability of water resources. During the last decades the overexploitation has lowered the groundwater level. The paper presents the results of artificial recharge in the aquifer system of Larisa prefecture through injection borehole and trench. The experiments took place during the period March - April 2006. The field experiments provided useful guidance on the planning of pilot tests, data monitoring and analysis, which can also be applied to other regions with similar hydrogeological conditions. Finally, this work confirms that groundwater recharge using the wintertime torrential flows is an environmentally acceptable solution, as part of an integrated water resources management strategy.